Money, the price level, and interest rates : an introduction to monetary theory - Makinen, Gail E. (Englewood Cliffs, N.J. : Prentice-Hall, 1977)
This book discuses the role of the money supply in Keynesian and Classical monetary theory and each was be analyzed. It also examines the theoretical foundations underlying monetary policy and macro theory.
Includes index.
Includes bibliographies reference p.433-435
usc 04/08/2017
Loans
Keywords: Money